A highly enantioselective Michael reaction between α, β-unsaturated ketones and malonic acid half-thioesters. (20th May 2015) - Ren, Qiao; Gao, Tao; Li, Wenjun; Wan, Li; Hu, Yimin; Peng, Yanhong; Sun, Shaofa; Hu, Liqiang; Wu, Minghu; Guo, Haibing; Wang, Jian
Abstract : An organocatalytic Michael reaction of enones and malonic acid half thioesters catalyzed by a chiral amine has been developed. Abstract : We disclose herein an efficient enantioselective organocatalytic Michael reaction between α, β-unsaturated ketones and malonic acid half thioesters (MAHTs). The reactions are catalyzed by a primary amine to generate Michael addition products in good to excellent yields (62–87%) with high to excellent enantioselectivities (80–98%).